In vitro Investigation of Ingavirin® Efficacy Against Influenza B Virus - S. YA. Loginova; S. V. Borisevich; I. A. Semenova; G. V. Borisevich; V. A. Maksimov; V. P. Bondarev; V. E. Nebolsin (Антибиотики и Химиотерапия)
The experimental investigation of Ingavirin® activity against influenza B virus showed that in concentrations 100 and 200 mcg/ml it was efficient in inhibition of the virus reproduction: the cytopathic effect was lowered by 75%, the level of the pathogen accumulation in the MDCK cell culture was decreased by more than 2.0 lg and the formation of the virus specific hemagglutinin was inhibited by more than 90%.